Il soffitto ligneo cassettonato della basilica di San Lorenzo a Firenze - Fedeli, Francesca (Opus Incertum, 2018)
This paper, accompanied by an abundant graphic and photographic documentation, aims at examining the historical events related to the construction of the coffered ceiling of the basilica of San Lorenzo in Florence, as well as the techniques used during its execution. Since there had been as yet no systematic study of these works, the restoration carried out between 1994 and 1999 under the Superintendency for the Environmental and Architectural Heritage of the provinces of Florence, Pistoia and Prato provided an excellent opportunity for their study and understanding. The consultation of archival and photographic-documentary material regarding the restoration allowed to examine and understand the construction techniques used. Under their current ivory-white colouring, which dates from the 19th century, two other colours were found: one pale-blue, extended throughout the entire surface of the ceiling, derived from the 1739 restoration under the Electress of the Palatinate, and another from the 15th century which was found only in some panels. Based upon literary sources an attempt was made to determine the building phases of the ceiling, relating them to those regarding the entire structure of San Lorenzo; additionally, the structure of the ceiling itself was studied and compared to other wooden structures from that period.